Muslim secular democracy : voices from within - Rahim, Lily Zubaidah; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2013)
The book offers a nuanced and innovative analyses of the emergence of an inclusive secular democratic state paradigm which incorporates the sacred within the framework of secular democracy in the Muslim World.
Keywords: Philosophy; Islam; Religion and sociology; Comparative politics; Political philosophy; Social sciences -- Philosophy